1969
DOI: 10.2337/diab.18.11.773
|View full text |Cite
|
Sign up to set email alerts
|

Relation of the Course of Retinopathy to Control of Diabetes, Age, and Therapeutic Agents in Diabetic Japanese Patients

Abstract: Follow-up results of the progression of diabetic retinopathy in 364 patients who attended the Diabetes Clinic of the Third Department of Internal Medicine (University of Tokyo) regularly for more than two years were analyzed in relation to their degree of control, age and therapeutic agents. Ophthalmologic examinations were performed by two ophthalmologists without referring to other data.In 289 untreated cases, retinopathy at the initial visit was more frequent and more severe when known duration of diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1976
1976
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 6 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…It is a wellestablished fact that the frequency of diabetic retinopathy among diabetics depends upon both the duration of diabetes and the pa tient's level of diabetic control [1][2][3][4][5][6][7][8]. It has also been confirmed that if the duration of the disease in 2 patients with diabetes melli tus is equal, the frequency of occurrence of diabetic retinopathy depends on the level of diabetic control [5,9,10].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is a wellestablished fact that the frequency of diabetic retinopathy among diabetics depends upon both the duration of diabetes and the pa tient's level of diabetic control [1][2][3][4][5][6][7][8]. It has also been confirmed that if the duration of the disease in 2 patients with diabetes melli tus is equal, the frequency of occurrence of diabetic retinopathy depends on the level of diabetic control [5,9,10].…”
Section: Introductionmentioning
confidence: 91%
“…As the most powerful risk factor for diabetic retinopathy the duration of diabetes has been reported [1][2][3][4][5][6][7][8]. However, the present study was undertaken to control this factor so that the duration of both groups was equal.…”
Section: Demographic Featuresmentioning
confidence: 99%
“…Among 14 prospective studies in patients with established retinal or glomerular lesions [21,22,35,[37][38][39][40][41][42][43][44][45][46][47][48] 4 drew negative conclusions. The UGDP study has just been mentioned [35].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…All other studies have demonstrated that good or very good control slows down the rate of deterioration of established lesions [21,22,37,40,[43][44][45][46][47][48].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…During the last three decades many clinical investigations have been undertaken in various parts of the world to determine if the incidence of microangiopathy is related to the degree of control of the diabetes [46]. With only a few exceptions [47] these studies have indicated that microvascular disease is less common in well controlled diabetics than in those in whom a less careful regimen of therapy is maintained [48][49][50][51][52]. Perhaps foremost in these clinical assessments is the ambitious longterm prospective study of Pirart and his collaborators [52] which has shown that diabetic capillary disease is closely related to the degree of glycemic control.…”
Section: Metabolic Hypothesis Of Diabetic Microangiopathymentioning
confidence: 99%